Economic Freedom and Economic Crisis - Christian Bjørnskov (Research Institute of Industrial Economics (IFN), 2015)
In this paper, I explore the politically contested association between the degree of capitalism, captured by measures of economic freedom, and the risk and characteristics of economic crisis. After offering some brief theoretical considerations, I estimate the effects of economic freedom on crisis risk in the post-Cold War period 1993-2010. I further estimate the effects on the duration, peak-to-trough GDP ratios and recovery times of 212 crises across 175 countries within this period. Estimates suggest that economic freedom is robustly associated with smaller peak-to-trough ratios and shorter recovery time. These effects are driven by regulatory components of the economic freedom index.
Keywords: O11; O43; P16; 330; Crisis; Economic freedom; Institutions